Investigating General Self-Efficacy and Teachers’ Professional Identity of Yogyakarta EFL Teachers - Wati, Rona Erlina; Kuswandono, Paulus; Ena, Ouda Teda (Universitas Negeri Semarang, 2024)
Professional identity is the main key construct that cannot be separated from teacher career development. Despite the large number of studies examining professional identity, its relationship with work-related behavior at career stages and their psychological aspects such as self-efficacy has not been extensively investigated, especially in Indonesia. The purpose of this study is to look at the correlation between teachers' professional identity and their general self-efficacy. Participants are EFL instructors from the primary to university level in Yogyakarta. The mixed method framework was used to acquire the data with a questionnaire and interview. An altered version of the General Self-Efficacy (GSE) and Teacher Professional Identity Scale (TPIS) questionnaire was used to gather quantitative data. According to the findings of this study, the average score for General Self-Efficacy (GSE) is 40.1333, while the average score for Teacher Professional Identity (TPI) is 55.8667. The Pearson correlation test findings show a modest link between GSE and TPI in this study, with a correlation value of 0.459.